2022
DOI: 10.1088/1361-6471/ac58b0
|View full text |Cite
|
Sign up to set email alerts
|

Fast-timing lifetime measurements of the 33/2+ and 25/2 states in 189Hg: oblate excitations

Abstract: The lifetimes of the $I^{\pi}=33/2^{+}$ and $I^{\pi}=25/2^{-}$ states with $E_x=2674.6$ keV and $E_x=1917.3$ keV, respectively, in $^{189}$Hg have been determined by using the fast-timing techniques with the HPGe and LaBr$_{3}$:Ce array via the $^{175}$Lu($^{19}$F,5$n$)$^{189}$Hg reaction at a beam energy of 100 MeV. The deduced $B(E2)$ strengths have been discussed in relation to the systematics of the previously reported $B(E2)$ strengths in the heavy mercury isotopes. The transition quadrupole moments $Q_t$… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Though, a number of lifetime measurements were performed in the even-even isotopes of Hg nuclei of this mass region, the lifetime measurements in odd-A Hg isotopes region are very rare. Earlier in [30] Y. Zheng, et al reported the lifetimes of (propsed) isomeric states 33/2 + and 25/2 + in 189 Hg. Also in 191 Hg, Jin H, et al [31] reported lifetimes of a few low spin states of the yrast band measured via recoil distance Doppler-shift techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Though, a number of lifetime measurements were performed in the even-even isotopes of Hg nuclei of this mass region, the lifetime measurements in odd-A Hg isotopes region are very rare. Earlier in [30] Y. Zheng, et al reported the lifetimes of (propsed) isomeric states 33/2 + and 25/2 + in 189 Hg. Also in 191 Hg, Jin H, et al [31] reported lifetimes of a few low spin states of the yrast band measured via recoil distance Doppler-shift techniques.…”
Section: Introductionmentioning
confidence: 99%